2008
DOI: 10.1007/s11182-009-9143-5
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature superelasticity in CoNiGa, CoNiAl, NiFeGa, and TiNi monocrystals

Abstract: аt. %) monocrystals. It has been shown that the superelastic temperature range depends on the crystal orientation and reaches a maximum for [001]-oriented crystals. In monophase crystals of Co (at. %), segregation of dispersion particles takes place at test temperatures T > 623 K. A criterion for high-temperature superelasticity has been proposed which implies the attainment of high strength of the high-temperature phase due to a proper choice of the crystal orientation, deviation from stoichiometry, and segre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 32 publications
6
25
0
Order By: Relevance
“…They are thought to be responsible for a high transformation temperature [7]. The same behavior was found in the crystals grown in our laboratory in which fcc cobalt solid solution nanoprecipitates [8] or hexagonal close packed (hcp) cobalt solid solution nanoprecipitates [9] were observed.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…They are thought to be responsible for a high transformation temperature [7]. The same behavior was found in the crystals grown in our laboratory in which fcc cobalt solid solution nanoprecipitates [8] or hexagonal close packed (hcp) cobalt solid solution nanoprecipitates [9] were observed.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies on the Co 38 Ni 33 Al 29 alloy demonstrated strong dependence of its transformation properties on the thermomechanical history, mainly the crystallization velocity [5,6] and the same behavior was noticed on similar alloys as well [7]. Since it is known that the transformation can be aected by the complex distribution of the fcc cobalt solid solution particles within the B2 matrix in the bulk material, we performed neutron diraction experiments both on powder material and on quickly solidied bulk polycrystals with homogeneous distribution of the fcc particles.…”
Section: Introductionsupporting
confidence: 52%
“…
Thermoelastic martensitic transformations (MT) during cooling/heating and under loading give rise to functional properties such as the shape memory effect and superelasticity [1][2][3][4]. Fe -28% Ni -17% Co -11.5% Al -2.5% Ta -0.05% B (at.%) disordered iron-based alloys suggested by Y. Tanaka et al in 2010 [5] have high strength, anomalously high superelasticity (of the order of 13%) caused by the γ-α′ MT under loading, good plasticity, and high damping ability in the polycrystalline state.
…”
mentioning
confidence: 99%
“…In Co 41 Ni 32 Al 27 single crystals, 3.3% magnetoinduced deformation is observed under the condition of simultaneous action of external stresses and magnetic field [1]. In quenched Co-Ni-Al single crystals oriented along [001] there is high-temperature superelasticity during tensile deformation up to the temperature 580 K with the value of reversible deformation being up to 7.0% [2][3][4]. The high-temperature phase of this alloy has a large region occupied by two phases and consists of their mixtur: В2-phase and γ-phase with an fcc-lattice not undergoing any MT but increasing plasticity of the brittle intermetallic compound [5].…”
Section: Introductionmentioning
confidence: 99%